Nitrogen Uptake Efficiency and Total Soil Nitrogen Accumulation in Long-Term Beef Manure and Inorganic Fertilizer Application - Peter Omara; Lawrence Aula; William R. Raun (International Journal of Agronomy)
Livestock manure is a common soil amendment for crop-livestock production systems. However, the efficiency of crop nitrogen (N) uptake from the manure-amended soil may not equate with that from inorganic N sources. The objective of this paper was to determine the efficiency of N uptake, grain yield, and total soil nitrogen (TSN) accumulation in beef manure-amended soil compared to the inorganic N fertilizer-amended soil. Data (1990–2015) from a long-term continuous winter wheat (Triticum aestivum L.) fertility experiment at Stillwater in Oklahoma, USA, were used in this report. Three of the six “Magruder Plot” treatments used in this study were manure, NPK plus lime (NPKL), and a check (no nutrients applied). Pre-plant N, P, and K were applied annually at 67, 14.6, and 27.8 kg·ha−1, respectively, while beef manure was applied every 4 years at 269 kg N·ha−1. The results indicated that grain N uptake in the manure treatment (48.1 kg·ha−1) was significantly (p<0.05) lower than that in the NPKL treatment (60.2 kg·ha−1). This represents 20.1% efficiency of inorganic N uptake than the manure N uptake. The average grain yield (1990–2015) from the manure and NPKL treatments was 2265.7 and 2510.5 kg·ha−1, respectively, and was not significantly different. There was a trend of TSN increase over the study period for both manure and NPKL treatments. The average TSN from manure and NPKL treatments was 0.92 and 0.91 g·kg−1 soil, respectively, and was not significantly different. While no significant difference between manure and NPKL grain yield was observed, there was a significantly lower uptake efficiency of manure N compared to inorganic N. Furthermore, the low uptake efficiency of the manure N could suggest a potential for environmental pollution. Appropriate timing and application rate of manure N sources could optimize crop use efficiency and limit potential threat to the environment.